Validity of Property Sale and Purchase Agreement between Residents in Taman Duren Sawit Housing with Developer PT Altan Karsaprisma as a Result of a Lawsuit by a Third Party - Muhammad Ihab Ramadhan; Ridha Wahyuni (Journal La Sociale, 2024)
This research aims to examine the validity of land and building sales and purchase agreements between residents at the Taman Duren Sawit Housing Complex (buyers) and developers (sellers), due to a lawsuit by a third party. This research is normative juridical, which uses a statutory approach (statute approach) and a case approach. The results of this research indicate that the developer as the seller has violated the objective conditions for the validity of the agreement, especially the conditions of "a certain thing" and the conditions of "halal causes", by selling objects whose ownership is still in dispute and there is no transparency regarding the legal status of the land of the sale and purchase object, which is still in dispute. Therefore, the agreement made is considered null and void by law. The legal remedy that can be taken by the buyer is to file an unlawful act lawsuit with the local district court based on Article 1365 of the Civil Code. This research concludes that the land and building sale and purchase agreement entered into by the parties is null and void because it has violated the terms of "a certain thing" and the terms of "halal causes" while the legal remedy that can be taken by buyers in good faith are to file a lawsuit. unlawful acts to the local district court.